Chronic bronchitis without airflow obstruction, asthma and rhinitis are differently associated with cardiovascular risk factors and diseases. - Marcello Ferrari; Elia Piccinno; Alessandro Marcon; Pierpaolo Marchetti; Lucia Cazzoletti; Pietro Pirina; Salvatore Battaglia; Amelia Grosso; Giulia Squillacioti; Leonardo Antonicelli; Giuseppe Verlato; Giancarlo Pesce (PLoS ONE, 2019)
BACKGROUND AND OBJECTIVES:Cardiovascular and respiratory diseases can frequently coexist. Understanding their link may improve disease management. We aimed at assessing the associations of chronic bronchitis (CB), asthma and rhinitis with cardiovascular diseases and risk factors in the general population. METHODS:We used data collected in the Gene Environment Interactions in Respiratory Diseases study, an Italian multicentre, multicase-control study. Among 2463 participants (age 21-86, female 50%) who underwent standardized interviews, skin prick and lung function tests, we identified 254 cases of CB without airflow obstruction, 418 cases of asthma without CB, 959 cases of rhinitis alone, and 832 controls. The associations of respiratory diseases with reported cardiovascular risk factors (lifestyles, hypertension, dyslipidaemia), heart disorders (myocardial infarction, coronary thrombosis, angina, aorta or heart surgery) and intermittent claudication were estimated through relative risk ratios (RRR) by multinomial logistic regression models. RESULTS:Compared to controls, CB cases were more likely to be heavy smokers, alcohol consumers, physically inactive, and to suffer from hypertension or dyslipidaemia; rhinitis cases were less obese but more likely to have hypertension. Asthma was significantly associated with current smoking. After adjusting for cardiovascular risk factors, heart disorders were associated with CB (RRR[95%CI]: 1.58[1.12-2.22]) and rhinitis (1.35[0.98-1.85]) and intermittent claudication was associated with CB (3.43[2.52-4.67]), asthma (1.51[1.04-2.21]) and rhinitis (2.03[1.34-3.07]). CONCLUSIONS:CB, asthma and rhinitis were associated with cardiovascular risk factors and diseases. In particular, CB shared with cardiovascular diseases almost all risk factors and was strongly associated with a higher risk of heart disorders and intermittent claudication.